Construction of a novel cuproptosis-related gene signature and integrative analyses in cholangiocarcinoma - Liye Wang; Pan Li; Shuai Gong; Lina Pang; Mingyu Li; Chi Zhang; Shengli Zhang; Xiaoke Zhang; Guozhong Jiang; Wei He (Heliyon)
Background: Cuproptosis is a unique form of cell death that is dependent on copper, which is fundamentally different from other recognized forms of cell death. However, the molecular and immune characteristics in cuproptosis-defined subgroups of cholangiocarcinoma (CCA) remain to be further illustrated. Methods: We conducted a comprehensive investigation into the genetic and transcriptional variation, prognostic significance, and expression profiles of 16 cuproptosis-related genes (CRGs). To construct a prognostic signature based on differentially expressed genes between molecular subtypes, we employed LASSO and multivariate Cox regression analyses. We then assessed the values of this signature in prognostic prediction, immune infiltration, and therapeutic responses in CCA. The robustness of the signature was further validated in the GEO and IMvigor210 cohorts. Additionally, qRT-PCR and Western blotting (WB) were utilized to confirm the expression of the signature genes across different cell lines. Results: A total of 16 CRGs were analyzed revealed differentially expressed, and two CRG-related clusters were identified, which displayed contrasting survival times.Then, a robust cuproptosis-related risk model was established and was an independent prognostic factor for CCA, which was further validated across two external cohorts. Low-risk patients had a better overall survival than high-risk patients. The comprehensive results showed that a low-risk score was correlated with metabolism-related pathways, high infiltration of CD8 T cells, B cells, and M1 macrophages, active immunity and less aggressive phenotypes, high chemotherapeutic sensitivity, and more benefit from immunotherapy. In contrast, a high-risk score was associated with cancer and metastasis-related pathways, high infiltration of M2 macrophages, high expression of immune checkpoint genes, suppressive immunity and more aggressive phenotypes, and less benefit from chemotherapeutic and immunotherapy. In addition, the critical CRGs were further validated through qRT-PCR and WB. Conclusions: We developed a novel risk model for CCA patients, which serves as a promising biomarker for distinguishing prognosis as well as molecular and immune characteristics.